The potential mechanisms and application prospects of non-coding RNAs in intervertebral disc degeneration - Jiang, Chao; Chen, Zhe; Wang, Xiaohui; Zhang, Yongyuan; Guo, Xinyu; Xu, Zhengwei; Yang, Hao; Hao, Dingjun (Frontiers in Endocrinology, 2022)
Low back pain (LBP) is one of the most common musculoskeletal symptoms and severely affects patient quality of life. The majority of people may suffer from LBP during their life-span, which leading to huge economic burdens to family and society. According to the series of the previous studies, intervertebral disc degeneration (IDD) is considered as the major contributor resulting in LBP. Furthermore, non-coding RNAs (ncRNAs), mainly including microRNAs (miRNAs), long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs), can regulate diverse cellular processes, which have been found to play pivotal roles in the development of IDD. However, the potential mechanisms of action for ncRNAs in the processes of IDD are still completely unrevealed. Therefore, it is challenging to consider ncRNAs to be used as the potential therapeutic targets for IDD. In this paper, we reviewed the current research progress and findings on ncRNAs in IDD: i). ncRNAs mainly participate in the process of IDD through regulating apoptosis of nucleus pulposus (NP) cells, metabolism of extracellular matrix (ECM) and inflammatory response; ii). the roles of miRNAs/lncRNAs/circRNAs are cross-talk in IDD development, which is similar to the network and can modulate each other; iii). ncRNAs have been attempted to combat the degenerative processes and may be promising as an efficient bio-therapeutic strategy in the future. Hence, this review systematically summarizes the principal pathomechanisms of IDD and shed light on the therapeutic potentials of ncRNAs in IDD.